2023
DOI: 10.1111/tpj.16368
|View full text |Cite
|
Sign up to set email alerts
|

Embryo sac development relies on symplastic signals from ovular integuments in Arabidopsis

Abstract: SUMMARYOvules are female reproductive organs of angiosperms, consisting of sporophytic integuments surrounding female gametophytes, that is, embryo sacs. Synchronization between integument growth and embryo sac development requires intracellular communication. However, signaling routes through which cells of the two generations communicate are unclear. We report that symplastic signals through plasmodesmata (PDs) of integuments are critical for the development of female gametophytes. Genetic interferences of P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 58 publications
(105 reference statements)
0
1
0
Order By: Relevance
“…It has been speculated that this tissue serves multiple roles in seed development, such as providing the necessary nutrients and supporting embryo and endosperm development, based on its strategic location and cytological characteristics. Consistent with this notion, a recent study revealed the significance of symplastic signals through plasmodesmata of integuments for the pre-fertilization development of the embryo sac 55 . In addition, another recent research demonstrated that micropylar integumentary-tapetum-generated gibberellin serves as a maternal signal regulating PCD initiation in the embryonic suspensor through the NtGID1-NtCRF1-NtCYS-NtCP14 signaling cascade 56 .…”
Section: Discussionmentioning
confidence: 62%
“…It has been speculated that this tissue serves multiple roles in seed development, such as providing the necessary nutrients and supporting embryo and endosperm development, based on its strategic location and cytological characteristics. Consistent with this notion, a recent study revealed the significance of symplastic signals through plasmodesmata of integuments for the pre-fertilization development of the embryo sac 55 . In addition, another recent research demonstrated that micropylar integumentary-tapetum-generated gibberellin serves as a maternal signal regulating PCD initiation in the embryonic suspensor through the NtGID1-NtCRF1-NtCYS-NtCP14 signaling cascade 56 .…”
Section: Discussionmentioning
confidence: 62%